Association of intrathecal pleocytosis and IgG synthesis with axonal damage in early MS. Issue 3 (May 2020) - Engel, Sinah; Steffen, Falk; Uphaus, Timo; Scholz-Kreisel, Peter; Zipp, Frauke; Bittner, Stefan; Luessi, Felix
Abstract : Objective: To investigate the association of serum neurofilament light chain (sNfL) levels with CSF parameters in clinically isolated syndrome (CIS) and early relapsing-remitting MS (RRMS), taking into account radiologic and clinical parameters of disease activity. Methods: Simultaneously collected serum and CSF samples of 112 untreated patients newly diagnosed with CIS or RRMS were included in this cross-sectional study. CSF parameters were obtained as part of routine diagnostic tests. sNfL levels of patients and of 62 healthy donors were measured by highly sensitive single molecule array (SiMoA) immunoassay. Results: Patients with RRMS (n = 91, median 10.13 pg/mL, interquartile range [IQR] 6.67–17.77 pg/mL) had higher sNfL levels than healthy donors (n = 62, median 5.25 pg/mL, IQR 4.05–6.81 pg/mL, p < 0.001) and patients with CIS (n = 21, median 5.69 pg/mL, IQR 4.73–9.07 pg/mL, p < 0.001). Patients positive for oligoclonal bands (OCBs) (n = 101, median 9.19 pg/mL, IQR 6.34–16.38 pg/mL) had higher sNfL levels than OCB-negative patients (n = 11, median 5.93 pg/mL, IQR 2.93–8.56 pg/mL, p = 0.001). sNfL levels correlated with CSF immunoglobulin G (IgG) levels ( r = 0.317, p = 0.002), IgG ratio (QIgG) ( r = 0.344, p < 0.001), and CSF leukocyte count ( r = 0.288, p = 0.002). In linear regression modeling, the CSF leukocyte count combined with the number of contrast-enhancing lesions in MRI predicted sNfL levels best. Conclusions: In active MS, sNfL levels correlate with intrathecal pleocytosis and IgG synthesis, indicating that axonal damage is associated with both acute and chronic CNS-intrinsic inflammation.